EFFECT OF SOIL STIFFNESS AND GROUND DISPLACEMENT IN EARTHQUAKE RESPONSE OF BRIDGES WITH PILE FOUNDATION - R. Mahmudur; K. Izuka; K. Imamura; K. Koga; T. Ohtsuka; G. Aramaki (Lowland Technology International, 2001)
Dynamic analysis was carried for earthquake response of prototype bridge structure with pile foundation in clay soil with sand base. Analysis was carried out for different soil stiffness parameter, Vs (shear wave velocity)- value using "Single input model" which does not consider the ground displacement. It was found that with increasing soil stiffness, eefect of ground displacement on response becomes smaller and the two models yielded similar results. Consideration of ground displacement has great effect in earthquake response for clay with shear velocity, Vs less than 100 m/sec i.e. for soft clay. Vs-value of 150 m/sec may be considered the critical velocity after which consideration of ground displacement has much less effect and thus simpler "Single input model" may be used. This corresponds to cohesion, cu value of 60 kPa and N- value of 4 approximately. It was also shown that strain dependence of shear modulus and damping have significant effect on displacement of the soil deposit.